Fixed Point Theorems and Uniqueness of the Periodic Solution for the Hematopoiesis Models - Jun Wu; Yicheng Liu (Abstract and Applied Analysis)
We present some results to the existence and uniqueness of the periodic solutions for the hematopoiesis models which are described by the functional differential equations with multiple delays. Our methods are based on the equivalent norm techniques and a new fixed point theorem in the continuous function space.